2011
DOI: 10.1007/s00705-011-0971-6
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a genome of a distant relative of chicken anemia virus reveals a new member of the genus Gyrovirus

Abstract: A 2.4-kb phi29 polymerase amplification product from serum of a diseased chicken was cloned and sequenced. The 2383-nucleotide sequence showed about 40% identity to a representative genome of chicken anemia virus (CAV), the only member of the genus Gyrovirus, family Circoviridae. The new genome had an organization similar to that of CAV: a putative 5' untranscribed region of about 400 nt followed by three partially overlapping open reading frames encoding VP1, VP2 and VP3 homologs. The amino acid identities be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 16 publications
0
58
0
Order By: Relevance
“…However, other potential members of the genus Gyrovirus have been recently discovered in humans and birds. These novel gyroviruses (GyVs) have been identified in human skin (human gyrovirus (HGyV) [74]) and feces (GyV3 through GyV6; [8,61,62]), chicken serum (avian gyrovirus 2 (AGV2) [66]) and meat (GyV4 and GyV7; [8]) as well as spleen and uropygial gland tissues from sea birds (GyV8; [39]). Since HGyV and AGV2 may represent the same species [61], the genus Gyrovirus should soon be updated to reflect at least eight viral species.…”
Section: Reassignment Of the Genus Gyrovirus To The Family Anelloviridaementioning
confidence: 99%
“…However, other potential members of the genus Gyrovirus have been recently discovered in humans and birds. These novel gyroviruses (GyVs) have been identified in human skin (human gyrovirus (HGyV) [74]) and feces (GyV3 through GyV6; [8,61,62]), chicken serum (avian gyrovirus 2 (AGV2) [66]) and meat (GyV4 and GyV7; [8]) as well as spleen and uropygial gland tissues from sea birds (GyV8; [39]). Since HGyV and AGV2 may represent the same species [61], the genus Gyrovirus should soon be updated to reflect at least eight viral species.…”
Section: Reassignment Of the Genus Gyrovirus To The Family Anelloviridaementioning
confidence: 99%
“…Most recently, novel members of the Gyrovirus genus have been discovered in diseased chicken (Rijsewijk et al, 2011), but also in human faeces (Phan et al, 2012) and in healthy blood donors as well (Biagini et al, 2013a). The positive fish samples examined in our survey originated from 142 TARJÁN et al Hungarica 62, 2014 apparently healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Sarker et al (2014) reported quasispecies variants and recombination events in an outbreak of emerging beak and feather disease virus (BFDV) that caused psittacine beak and feather disease. Chicken anemia virus (CAV) was the only known representative of the Gyrovirus genus, novel avian gyrovirus 2 (AGV2) and genetic variants of AGV2 were reported in chickens (Rijsewijk et al, 2011;Dos Santos et al, 2012). Avian orthoreoviruses have been associated with a variety of diseases in chickens.…”
Section: Classical Methods For Study Of Virus Diversitymentioning
confidence: 99%